Effect of Protein on Growth and Carcass Yield of Emu - Blake, J.P.; Hess, J.B. (International Journal of Poultry Science, 2004)
Seventy-two emu of mixed sex (mean age 107 d) were randomly distributed among six pens (4.2 x 24.2 m) with 12 birds/pen. Two pens each were fed either a 14, 16, or 18% protein (2860 kcal/kg) corn-soybean meal diet from 0 - 176 d on test. From 176 - 248 d on test, a 14% protein finisher diet containing either 2860 kcal/kg or 3080 kcal/kg was fed to each of two pens fed the same protein level prior to day 176. Body weights were obtained at 0, 15, 30, 43, 79, 108, 135, 176 and 248 d on test for each bird, while ad libitum feed consumption was measured for each pen. At 273 d, five birds were selected for slaughter from each pen based on mean body weight and carcass, fat, neck, bone, fan and fillet muscle, second muscle and ground meat weights were obtained. Body weight gain was less (P<0.01) in birds fed the 14% protein diet during the 176 day experimental period and was not affected by energy level during the finishing period. Cumulative feed efficiency (kg feed/kg gain) for the 248 d period for birds fed 14, 16, or 18% protein was 12.08, 11.05 and 10.92, respectively (P>0.05). Carcass weights and yields were unaffected by treatment. Carcass weights for females were greater (P<0.05) than for males (23.17 vs. 21.57 kg). Average amounts of fat, bone, neck, fan and fillet muscles, second muscles and ground meat as a percentage of carcass yield remained unaffected by treatment (P>0.05) (although values for females were numerically greater than for males) and averaged 18.9, 18.2, 3.8, 8.6, 18.8 and 27.5%, respectively. Results indicate that emu fed a low protein diet exhibit the ability to compensate for growth and carcass yield.